Reconciling and rehumanizing indigenous-settler relations: an applied anthropological perspective - Ferrara, Nadia (Lexington Books, 2015)
Building bridges -- Being the other -- Rebuilding trust through dialogic exchange -- Translating lived realities -- Personal lived reality : opening of my self -- Engaging in reconciliation -- Ethical responsibility -- Conclusion : towards intergenerational reconciliation -- Epilogue : coming home--bi-giiwe